(untitled) (Педагогіка вищої та середньої школи, 2002)
The article dwells upon the problem of the humanistic іdea formation while teaching foreign literature. The notion of the humananistan ideal is analyzed as well as the ways of its formation while studying works created by world-known men of letters.